2020
DOI: 10.22515/shirkah.v5i2.309
|View full text |Cite
|
Sign up to set email alerts
|

Education Level, Spiritual Intelligence, and Love of Money: Do They Correlate to Ethical Perception?

Abstract: The aim of this study is to shed some light on the impact of education level, spiritual intelligence, and love of money on ethical perception of accounting students which still remains unexplored thus far. The data were taken from 100 accounting students of several universities in Semarang Indonesia as the respondents. The data were further analyzed by employing PLS (Partian Least Square). The data analyses revealed several compelling results. First, there was no significant impact of education level on ethica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
(20 reference statements)
1
0
0
Order By: Relevance
“…We assumed that money attitude is negatively correlated with spiritual well-being; that is, lower scores on money attitude in the particular dimensions are associated with high levels of spiritual well-being in the specific domains, and the findings confirmed this assumption. The findings of this current study are in line with the empirical findings of Istiariani and Arifah (2020). Kasser and Ryan (1996) and Sirgy (1998) found that lower levels of money attitude were associated with higher levels of subjective well-being.…”
Section: Discussionsupporting
confidence: 91%
“…We assumed that money attitude is negatively correlated with spiritual well-being; that is, lower scores on money attitude in the particular dimensions are associated with high levels of spiritual well-being in the specific domains, and the findings confirmed this assumption. The findings of this current study are in line with the empirical findings of Istiariani and Arifah (2020). Kasser and Ryan (1996) and Sirgy (1998) found that lower levels of money attitude were associated with higher levels of subjective well-being.…”
Section: Discussionsupporting
confidence: 91%
“…Hence, students with higher religiosity exhibit more ethical perceptions towards creative accounting (Jaya & Sukirno, 2020). Besides, spiritual intelligence positively affects students' ethical perceptions (Irma & Uliya, 2020). Sulistyowati et.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, PLS was selected for its effectiveness in validating variable models. (Irma & Uliya, 2020). 9.…”
Section: Methodsmentioning
confidence: 99%
“…Adhariani, 2020) (Istiariani et al, 2020). The results show that the level of education, socioeconomic status, and experience have a significant positive influence on the love of money.…”
Section: 2mentioning
confidence: 95%